Academic Society Scientific Paper Writing Training Poltekkes Kemenkes Palu: Pelatihan Menulis Karya Ilmiah Masyarakat Akademik Poltekkes Kemenkes Palu - Fahmi Hafid; Nasrul Nasrul; Taqwin Taqwin; Aminuddin Aminuddin; Muliani Muliani; Kadar Ramadhan; Yulianus Sudarman H Melangka; Heru Santoso Wahito Nugroho; Abdul Ganing (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Poltekkes Kemenkes Palu has 131 authors on the Sinta Kemendikbud website. There are still many authors who have not had a sinta score in the last three years. The aim of the training in writing scientific papers for the academic community at the Poltekkes Kemenkes Palu is to improve the ability to write quality scientific papers. The activity was carried out on January 4-5 2023 in the meeting room of the Center for Research and Community Service, the Ministry of Health, Palu Health Polytechnic. There were 4 resource persons and 41 participants, Lecturers of the Polytechnic of the Ministry of Health, Palu. The implementation method is through lectures, writing practice, practice using publish or perish and practice using Mendeley. The activity was held in the PPM Central Hall. The material is preparing scientific article manuscripts, practical writing of scientific articles, practice of citation of journal articles through publish or perish and publication using a letter of editor” is given. The results of the community service activities showed an increase in the publication of letters to editors by 14 articles published from 17 January to 5 May 2023. The conclusion of the activity was that participants were able to publish letter to editor articles. It is recommended that participants continue to practice writing skills and try to submit or publish manuscripts independently.